Depression and its Cure: A Drug Utilization Study from a Tertiary Care Centre of Western Nepal (Nepal Journal of Epidemiology, 2011)
Background: According to WHO, it is estimated that major depression would be the second most leading cause of disability in the world by 2020. Drug utilization study is defined as study of the marketing, distribution, prescription and use of drugs in a society highlighting on the resulting medical, social and economic consequences. The main objective of this study was to find the utilization pattern of antidepressants prescribed in a tertiary care centre with major depression in hospitalized patients of Western Nepal.Methods: A hospital based observational study was done between 1st October 2009 and 31st March 2010 at Psychiatry Ward of Manipal Teaching Hospital, Nepal. Both qualitative and quantitative data was collected from bed side. The outcome variables were essential drug, generic and trade, treatment, groups of antidepressants and antidepressants used. The explanatory variables were age, gender, monthly income, employment of the patient. Z test and logistic regression was used for the analysis. P-value < 0.05 was considered to be statistically significant. This is the first study done to understand the utilization pattern of antidepressant drugs in hospitalized patients in Nepal.Results: Among the 240 psychiatric patients studied, 38 (15.8%) cases were suffering from major depression. Male and female patients were 44.7% and 55.3% respectively, 95% CI [28.9, 60.5 and 39.5, 71.1]. Depression was more common in housewives (42.1%) followed by teachers 18.4% and students 10.5%. Fluoxetine was the commonest antidepressants to be prescribed 42.1% followed by Amitriptyline 26.3%, Trazodone 21.1% etc. Psychiatrists has a tendency of prescribing essential drugs if monthly income 10000, 2.63 times more in Hindus and 1.197 times more in Brahmins than any other ethnic groups. 9.179 times more tendency of prescribing antidepressants by trade names in case of unemployed patients as compared to employed patients in Nepal.Conclusion: According to the utilization pattern of antidepressants it was found that among the Selective serotonin reuptake inhibitors Fluoxetine was used relatively higher than conventional drugs like Tricyclic antidepressants, recommend that there is a trend of using Typical antidepressants drugs for depression rather than Newer antidepressants.DOI: http://dx.doi.org/10.3126/nje.v1i5.6152 Nepal Journal of Epidemiology 2011;1 (5):144-52